ZnO Electrodeposition on Boron-Doped Diamond: Effects of Zinc Precursor Concentration. (13th April 2015) - Gautier, Pierrick; Vallée, Anne; Etcheberry, Arnaud; Simon, Nathalie
Abstract : The cathodic electrodeposition of zinc oxide has been widely studied on various substrates in the last decades. The boron doped diamond (BDD) is a non conventional wide band gap semiconductor, which offers new possibilities as a substrate for this electrochemical deposition. Thus, in the present work, we study the deposition process performed with zinc chloride and dissolved oxygen as a precursor. The effect of zinc precursor concentration in a range of 0.2 to 5 mM is tested at 60°C. The current transient curves coupled with X-Ray Diffraction and Scanning Electron Microscopy analysis, reveal the effect of this parameter on the morphology of obtained ZnO/BDD deposits. Interestingly, the formation of ZnO pyramids was highlighted for the first time.